The sewing answer book : solutions to every problem you'll ever face, answers to every question you'll ever ask - Talbert, Barbara Weiland, 1947- (Storey Pub., 2010)
The perfect portable teacher for everyone from beginners turning on a sewing machine for the first time to experienced sewers seeking tips on how to embellish a blouse with tiny pintucks. This friendly, reassuring resource, written by sewing expert and educator Barbara Weiland Talbert, answers the questions, corrects the mistakes, and troubleshoots the nagging problems sewers encounter every time they sit down at the sewing machine or pick up a needle and thread.